Assessment of the clinicodemographic parameters and treatment outcomes of locally advanced and metastatic lung cancer cases – A retrospective study from northeast India - Satya Sadhan Sarangi; Munlima Hazarika; Partha S Roy; Nithin D Raj; Partha P Medhi; Anupam Sarma (Asian Journal of Medical Sciences, 2023)
Background: There are many lacunae in our current understanding of the shifting epidemiological trends of lung cancer as well as lack of data among Northeast Indian patients. Aims and Objectives: This study tried to assess the clinicodemographic and treatment outcomes of advanced lung cancer cases. Materials and Methods: This was a retrospective hospital-based study. Patients with histopathologically confirmed locally advanced and metastatic lung cancer and were registered at Dr. Bhubaneswar Borooah Cancer Institute between January and December 2017 who were included in the study. A record was made of patient demographic-, clinical-, and treatment-related parameters. Kaplan–Meier survival curves were obtained. A two-tailed P<0.05 was considered statistically significant. Results: Majority of the patients were elderly males (median=60 years), with a history of smoking in three quarter of them. Non-small-cell lung carcinoma (94%) type was the most common histology. About 93% of patients presented with TNM stage IV disease. The most common palliative chemotherapy (CT) regimen used was taxanes and platinum doublet (n=24, 35%). With a median follow-up of 6 months (range 0–37), the median progression-free survival and overall survival were 8 months and 10 months, respectively. The median survival was significantly longer in patients younger than 60 years. (13 months; P=0.021) and in those with non-small-cell histology (10 months). Conclusion: In this audit of resource-limited population with advanced lung cancer, palliative CT remains the mainstay of treatment. There is a further need to improve the survival of these advanced cases in a cost-effective manner.